THE INFLUENCE OF ORGANIZATIONAL CULTURE AND EMOTIONAL INTELLIGENCE ON WORK INVOLVEMENT MEDIATED BY EMPLOYEE INTERPERSONAL COMMUNICATION - Budi Alamsyah Siregar; Dewi Suma (SEAN Institute, 2023)
This study aimed to determine the effect of organizational culture and emotional intelligence on work involvement mediated by interpersonal communication—a total of 210 samples of finance company employees. Samples were selected proportionally by random sampling. Data was obtained through a questionnaire. The data analysis technique uses a structural equation model (SEM) with Smart-PLS version 3.0. The study results show that emotional intelligence is the variable that has the most significant influence in influencing employee work involvement. This study also found that organizational culture is the second most significant influence that can increase work engagement. The subsequent finding from this study is that interpersonal communication is not an influential mediating variable to bridge the increase in organizational culture and emotional intelligence on employee work engagement. Finance companies should be able to improve employees' emotional intelligence with indicators of self-knowledge, self-control, self-motivation, and empathy from employees. Employees are directed to realize their weaknesses and strengths, which can increase self-confidence and ability to solve problems in their work. Employees must be able to control themselves, not be selfish, control themselves, and be responsible. Employees must be able to think of positive things, not give up quickly, and be able to motivate themselves. Employees who increase their work involvement will be able to feel what other people feel, help co-workers who are having problems at work, can motivate co-workers. The benefits of employee involvement can be felt if employees can become problem solvers and are willing to accept open criticism for criticism from both leaders and co-workers.